Interpretations of the Determinants of Health from Feminist Perspectives - Guille Magaly Meneses Maqueda (Mexican Journal of Medical Research ICSA)
In this paper, an analysis is carried out on the model of health determinants proposed by Lalonde, from the point of view of feminist studies with the aim of reflecting on the conditions of women that must be taken into account in each of the determinants of health to contribute to the understanding of the importance of gender as an analytical category in women's well-being processes. Health care practices are determined by a series of norms created under an androcentric perspective that have excluded the specificities of women, generating inequalities and stigmas towards their discomforts.